New Black Fungus Gnats (Diptera, Sciaridae) of North America Part I. Genus Scatopsciara Edwards, 1927 - Mohrig, Werner; Kauschke, Ellen (Zootaxa, 2016)
In the Nearctic region the genus Scatopsciara includes 37 species. Herein these species are diagnosed, keyed and distribution data provided. Twenty six species are known exclusively from the Nearctic region. Eleven species have a Holarctic distribution. Nineteen species are described as new for science. These are: Scatopsciara abedabunae sp. n. (USA, Canada), Sc. adsilae sp. n. (USA), Sc. alawae sp. n. (USA), Sc. awanatae sp. n. (USA), Sc. awinitae sp. n. (USA, Canada), Sc. catoriae sp. n. (USA), Sc. chenoae sp. n. (USA), Sc. inesae sp. n. (USA), Sc. itumae sp. n. (USA), Sc. miakodae sp. n. (USA), Sc. praealawae sp. n. (USA), Sc. praeawanatae sp. n. (USA), Sc. subawanatae sp. n. (USA), Sc. subdendrotica sp. n. (Canada), Sc. subfratercula sp. n. (Canada), Sc. subgrossa (USA), Sc. subitumae sp. n. (USA), Sc. submiakodae sp. n. (USA) and Sc. tricuspidatula sp. n. (USA). The following five species are new for North America: Scatopsciara curviforceps Bukowski & Lengersdorf, 1936, Sc. geophila Tuomikoski, 1960, Sc. neglecta Menzel & Mohrig 1998, Sc. subciliata Tuomikoski, 1960 and Sc. ventrospinula Mohrig & Mamaev, 1983. Six species, included in Corynoptera so far were transferred to the genus Scatopsciara. These are Sc. armigera (Vilkamaa & Hippa, 2006), Sc. fratercula (Vilkamaa & Hippa, 2006), Sc. robustior (Vilkamaa & Hippa, 2006), Sc. vagula (Tuomikoski, 1960), Sc. fera (Mohrig & Heller, 1992) (in Heller & Mohrig, 1992) and Sc. nyxa (Mohrig & Menzel, 1992).